The impact of herding behavior on the performance of investment companies based on modern and post modern portfolio theory - Shahabeddin Shams; Amir Teymur Esfandirari Moghaddam (تحقیقات مالی, 2017)
In this research,by using statistical data of 24 accepted investment companies on a monthly basis, and by using Lakonishok model (1992) for the period 1388-1394, impact of herding behavior on the performance of the companies based on modern and post modern portfolio theory is examined. In order to analyze data and examine the hypothesis, after reviewing the static of variables, has been used by Generalized Method of Moments (GMM) and Generalized Least Squares (EGLS) methods of estimations. Results indicate that herding behavior in investment companies’ significant negative impact on performance criteria based on the theories of modern and post modern portfolio. In other words, herding behavior is negatively affected on all performance measures Jensen, Sharp, Trainer, Sortino, good potential, Omega, Trainer adjusted and Jensen adjusted